Risk modification on the part of managers - Perica Vojinić (Ekonomski Vjesnik, 2012)
The paper aims to determine how and how often Croatian managers modify the risk in business situations. The paper includes results of a survey conducted among the sample of managers employed at middle and senior management levels in Croatian companies. The sample consists of 81 managers. Descriptive statistics was used in the process. The hypothesis that managers are more prone to modify the risk than to make a simple choice between a safe or a risky alternative was confirmed. The results of a one-way analysis of variance suggest that there is a connection between a manager’s risk preferences and risk modification preferences. As expected, managers who choose risky alternatives are those who are likely to take a risk; managers undertaking a safe action are the least likely to take a risk, whereas those who modify risk are moderately risk prone. Methods of descriptive statistics were used to analyse the applicability of the prospect theory in local environment. The results suggest that Croatian managers in the hotel industry behave according to behaviour patterns advocated by the prospect theory. Namely, managers avoid risk in the gain domain, whereas they accept it in the loss domain.